A Bistable Microelectromechanical System Actuated by Spin‐Crossover Molecules. Issue 28 (10th May 2017) - Manrique‐Juarez, Maria D.; Mathieu, Fabrice; Shalabaeva, Victoria; Cacheux, Jean; Rat, Sylvain; Nicu, Liviu; Leïchlé, Thierry; Salmon, Lionel; Molnár, Gábor; Bousseksou, Azzedine
Abstract: We report on a bistable MEMS device actuated by spin‐crossover molecules. The device consists of a freestanding silicon microcantilever with an integrated piezoresistive detection system, which was coated with a 140 nm thick film of the [Fe(HB(tz)3 )2 ] (tz=1, 2, 4‐triazol‐1‐yl) molecular spin‐crossover complex. Switching from the low‐spin to the high‐spin state of the ferrous ions at 338 K led to a reversible upward bending of the cantilever in agreement with the change in the lattice parameters of the complex. The strong mechanical coupling was also evidenced by the decrease of approximately 66 Hz in the resonance frequency in the high‐spin state as well as by the drop in the quality factor around the spin transition. Abstract : Tiny changes with huge impact : Spin‐crossover molecules of [Fe(HB(tz)3 )2 ] (tz=1, 2, 4‐triazol‐1‐yl) were used to actuate a silicon microelectromechanical device. Switching from the low‐ to the high‐spin state of the ferrous ions led to reversible upward bending of a cantilever in agreement with the change in the lattice parameters of the complex (see picture), thus demonstrating the use of molecular‐scale movements for large‐scale mechanical work.